Construction des connaissances au cours d’une formation hybride - Nicolas Perrin; Artémis Drakos; Gaëlle Martin; David Piot (Revue d'anthropologie des connaissances)
This paper presents an approach to the design and analysis of training situations based on the case of hybrid training in higher education. It adopts a multi-scale approach to human activity, distinguishing three scales: the here and now, the configuration of collective activity, and the history of training. The analysis of activity allows the system to be redesigned between each training session. It also makes it possible to specify the three scales initially adopted for the design, because it is the relationship between these scales that makes it possible to specify their nature. This relationship is defined as a star-statement relationship in which the higher scales emerge from the lower scales and in turn constrain the latter. It is thus possible to specify the mutual determinations between the here and now, the configuration of collective activity and the history of formation.